Study skills for learning power - Hellyer, Regina; Robinson, Carol; Sherwood, Phyllis (Boston : Houghton Mifflin, 1997)
This book is about: The power of note taking; The power of reading for meaning; The power of Study-Reading; ...
Keywords: Study skills; Learning power; Study skills -- Handbooks, manuals, etc...